Cytotoxic pimarane-type diterpenes from the marine sediment-derived fungus Eutypella sp. FS46. Issue 4 (16th February 2017) - Liu, Hongxin; Zhang, Ling; Chen, Yuchan; Li, Saini; Tan, Guohui; Sun, Zhanghua; Pan, Qingling; Ye, Wei; Li, Haohua; Zhang, Weimin
Abstract: Two new pimarane-type diterpenes, scopararanes H-I (1 –2 ), along with five known ones (3 –7 ) were isolated from the culture broth of a marine sediment-derived fungus Eutypella sp. FS46, which was obtained from the South China Sea. Their structures were established by extensive spectroscopic analysis. All of them were evaluated for their cytotoxic activities against MCF-7, NCI-H460 and SF-268 tumour cell lines. Scopararane I (2 ) showed moderate inhibitory activities. Abstract :